Web platform design for environmental health: a case study in Colombia (2019)
Most of the existing platforms for Environmental health have been created from the point of view of only one of the actors. These approaches are mostly based on proprietary tools and do not integrate all the components associated with environmental health. This paper describes the design of a platform based on free software for environmental health called PSAM. Several actors were included during the design, including environmental and health authorities, community leaders, and community members. PSAM comprises diverse modules to collect data using mobile devices, analyze the collected information and predict the appearance of H. Pylori. Finally, PSAM allows sending SMS to the community for community empowerment. The proposed architecture and learned lessons can serve as the basis for other implementations in the field and can also contribute to Colombia’s government development of a platform for environmental health.